Efficacy of topical tacrolimus for the treatment of persistent pruritus ani in patients with atopic dermatitis - Ucak, Haydar; Demir, Betul; Cicek, Demet; Dertlioglu, Selma Bakar; Akkurt, Zeynep Meltem; Ucmak, Derya; Halisdemir, Nurhan (Taylor & Francis Ltd, 2013)
Background: Pruritus ani (PA) is defined as intense chronic itching affecting perianal skin. Objective: We aimed to determine the efficacy of topical tacrolimus treatment in atopic dermatitis (AD) patients who have PA. Methods: The study included 32 patients with AD who were suffering PA. Patients were randomized into two groups. In total, 16 patients used 0.03% tacrolimus ointment and 16 patients used vaseline as placebo. All groups applied topical treatments to their perianal area twice daily for 4 weeks. The treatments were then reversed for 4 weeks after a 2 weeks wash out period. Results: In total, 32 patients with AD who had refractory anal itching were enrolled in this study. None of the patients had obtained successful results with previous treatments. There was a statistically significant decrease in the recorded EASI, DLQI and itching scores for the tacrolimus group compared to the placebo group at weeks 4 and 6 of treatment (p < 0.05). Conclusion: Topical tacrolimus treatment was well tolerated and effective in controlling persistent PA in AD patients.
Keywords: anal itching; dermatology life quality index; eczema area and severity index; atopic dermatitis; pruritus ani; tacrolimus ointment